Part II : Critical assessment of financial sector reforms and liberalization of ASEAN 10+5 economies. - Tan, Kok Yew. (2008)
The Final Year Project “PART I: RANKING OF 2006 FINANCIAL SECTOR REFORMS AND LIBERALIZATION OF ASEAN 10+5 ECONOMIES” adopted the NTU-ISEAS Financial Reforms and Liberalization Indices (FRLRI) framework which quantifies an economy’s efforts and progress in the reforms and liberalization of the financial sector. This report, PART II: CRITICAL ASSESSMENT OF FINANCIAL SECTOR REFORMS AND LIBERALIZATION OF ASEAN 10+5 ECONOMIES, is a continuation from Part I, with its main objective set in accessing and monitoring the financial sector reforms and liberalization of the ASEAN 10+5 economies from 1993 to 2006.